Promoting Counselor Trainees’ Clinical Skill Development Using Virtual Reality Simulations - Amber L Pope; Chelsea Hilliard (Teaching and Supervision in Counseling, 2024)
Although research on virtual reality (VR) as a pedagogical tool within counselor education is scarce, the parallel use of VR in health sciences education indicates VR simulations may have similar utility and effectiveness in training counselors. This conceptual piece aims to assist counselor educators in building VR simulations for counselors-in-training (CITs). The authors review the research on VR usage in counselor education and explore the practical implications of VR simulations for training counselors. The authors describe the development and utilization of VR simulations across multiple stages of training in a counselor education master’s program to support CITs’ clinical skill development during the COVID-19 pandemic. Advantages, limitations, and diversity and equity considerations of VR simulation usage in counselor training are discussed.
Keywords: virtual reality; simulations; counselor education; counselor training